WASHBACK ANALYSIS OF STUDENTS’ PERCEPTION AND TEACHERS’ TEACHING MATERIAL OF ENGLISH NATIONAL EXAMINATION 2017 - Nahdia, Khilma (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
This final project is intended to investigate the washback of the English national examination based on the students‟ perception and teachers‟ teaching material. The research used descriptive qualitative methods as its research methodology. The study shows that the national examination brings positive and negative effects to both students and teachers. For the students, the national examination triggers them to study harder than usual. Nevertheless, the national examination still makes the students anxious due to its usefulness as the consideration of their next school level entrance, which, consequently, makes them give more attention only to the subjects tested in the national examination. Furthermore, for the teachers, the national examination makes them work hard to supply the students with various media, methods, and books in the teaching-learning process in order to make the students getting ready to face the national examination. Nonetheless, the national examination that only tested the reading and writing skills makes the teachers do not teach the English skills material equally. In conclusion, the washback of the English national examination in SMP N 12 Semarang shows the indication of both positive and negative washback effects of the national examination.